2009
DOI: 10.21829/azm.2009.252642
|View full text |Cite
|
Sign up to set email alerts
|

Biological and behavioral aspects of two laboratory strains of Ceratitis capitata (Diptera: Tephritidae): the influence of periodic introduction of wild flies in the colony

Abstract: ABSTRACT.The healthy maintenance of insects reared under laboratory conditions requires strategies to retain the natural characteristics of their life-histories traits. Rearing strategies include artificial selection to laboratory conditions, hybridization with compatible strains, and supplying the colony with wild individuals. We compared behavioral as well as life-history aspects of two laboratory strains of Ceratitis capitata Wiedemann (Diptera, Tephritidae) that had either been reared for 15-20 years under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Reflecting the results of the present study, Meats et al (2004) found that the egg load of an old Q-fly colony was higher than that of young colonies. Increase in egg production and reduced choosiness of oviposition site has been reported in laboratory-adapted colonies of C. capitata (Bravo & Zucoloto, 1998;Elaini et al, 2020;Joachim-Bravo et al, 2009;Vargas & Carey, 1989). Positive relationship between fecundity and domestication has also been reported in fruit flies including B. oleae (Rossi) (Ahmad et al, 2016) and A. ludens Loew (Cayol, 2000;Carey et al, 2005), as well as in insects from other taxa, including sweet potato weevil, Euscepes postfasciatus (Coleoptera: Curculionidae) (Shimoji & Miyatake, 2002).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Reflecting the results of the present study, Meats et al (2004) found that the egg load of an old Q-fly colony was higher than that of young colonies. Increase in egg production and reduced choosiness of oviposition site has been reported in laboratory-adapted colonies of C. capitata (Bravo & Zucoloto, 1998;Elaini et al, 2020;Joachim-Bravo et al, 2009;Vargas & Carey, 1989). Positive relationship between fecundity and domestication has also been reported in fruit flies including B. oleae (Rossi) (Ahmad et al, 2016) and A. ludens Loew (Cayol, 2000;Carey et al, 2005), as well as in insects from other taxa, including sweet potato weevil, Euscepes postfasciatus (Coleoptera: Curculionidae) (Shimoji & Miyatake, 2002).…”
Section: Discussionmentioning
confidence: 94%
“…Increase in egg production and reduced choosiness of oviposition site has been reported in laboratory‐adapted colonies of C . capitata (Bravo & Zucoloto, 1998; Elaini et al, 2020; Joachim‐Bravo et al, 2009; Vargas & Carey, 1989). Positive relationship between fecundity and domestication has also been reported in fruit flies including B .…”
Section: Discussionmentioning
confidence: 99%
“…Field-collected populations of insects experience genetic bottlenecks when used to establish laboratory colonies ( Boller 1972 , Hoffman and Ross 2018 ). Insects that survive colonization may not have fitness traits that were adaptive in the field, instead they become lab-adapted due to the selection pressures of their new environment ( Chambers 1977 , Joachim-Bravo et al 2009 ). They eventually tend to be less mobile ( Boller 1972 ), develop faster, and have a greater rate of reproduction than the source population ( Meats et al 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…Life-history parameters can be monitored to determine the degree of decline relative to previous time periods, particularly the proportion of mated females, pre-oviposition period, age-specific fecundity, percent egg eclosion, rate of immature development, mass or size of the insects, and ultimately the yield of viable adults ( Leppla 2009 ). At some threshold of minimal viability, the colony must be restored by adding insects from the source population with managed selection ( Joachim-Bravo et al 2009 , Sorensen et al 2012 , Hoffman and Ross 2018 ) or by replacing it entirely ( Mangan 2021 ). Adding insects without removing bottlenecks experienced by the founding population would not improve the colony.…”
Section: Introductionmentioning
confidence: 99%